ANGIOGENESIS ACTIVITY OF Chromolaena odorata L. LEAF EXTRACT GEL IN OPEN WOUNDS INCISION PHASE II OF RATS - Limbong, Ahmad Affandi; Mirnasari, Mirnasari; Dasrul, Dasrul; Ismy, Jufriady; Hidayat, Imam; Yusuf, M (Universitas Syiah Kuala, 2024)
This study aims to determine the effect of administering Chromolaena odorata L. leaf extract gel on increasing angiogenesis in the healing of open incisional wounds in rats (Rattus norvegicus). In this study, 27 healthy male rats, aged 3-4 months with a body weight of 150-200 g were used. The rats were anesthetized and incised in the back area with a size of 2x2 cm (WxL) and a depth reaching subcutaneous. The rats were divided into three groups (n= 9), the group only given gel (P0), the group of rats that were given 10% Chromolaena odorata leaf extract gel (P1), and the group of rats that were given 20% Chromolaena odorata leaf extract gel (P2). Collection of wound skin tissue samples for histopathological preparations was carried out on days 3, 7, and 14 after treatment, 3 individuals per group for each collection. The results showed that application of Chromolaena odorata leaf extract gel on P1 and P2 could increase angiogenesis significantly (P0.05) compared to P0 on days 3 and 7, but was not significantly different (P0.05) on day 14. The average angiogenesis in P1 and P2 on day 3 was similar, while on day 7 the average angiogenesis on P1 was significantly different compared to P2. It was concluded that administration of Chromolaena odorata leaf extract gel could increase angiogenesis in rats during phase II of the open incision wound healing process.